One-Pot, Two-Step Synthesis of Highly Functionalized 4-Indolyl/Pyrrolyl-Chromanes via a para-Quinone Methide Formation–1,8-Addition Sequence - Khatoon, Rafia; Jandial, Tanvi; Gupta, Anish; Kundan, Sujata; Sridharan, Vellaisamy (Synthesis, 2024)
An efficient one-pot, two-step synthesis of structurally diverse 4-indolyl-/pyrrolyl-chromanes was developed starting from o-propargylated salicylaldehydes, 2,6-dialkylphenols and indoles/pyrrole. This process begins with a sequential secondary amine-catalyzed formation of p-quinone methides followed by Brønsted acid catalyzed 1,8-addition with indoles/pyrrole to access the functionalized chromanes in high yields (up to 91%). This sequential reaction generates three new C–C bonds, shows high step- and atom-economy with only one molecule of water as the side product and gives access to complex molecular frameworks without the need for the isolation of the intermediates.
Keywords: heterocycles; 4-indolyl-chromanes; 4-pyrrolyl-chromanes; p-quinone methide; 1,8-addition